2019
DOI: 10.1093/jxb/erz251
|View full text |Cite
|
Sign up to set email alerts
|

Source–sink relationships during early crop development influence earliness of sugar accumulation in sugarcane

Abstract: The dynamics of tiller production and senescence modify early source–sink relationships in sugarcane and the thermal time from crop emergence to the end of the tiller mortality phase appears to be a key trait in identifying earliness of sucrose accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…It is known that structural polysaccharides make up the bulk of the plant and in critical periods of growth and development can be incorporated in metabolism, probably providing a photosynthesis-independent flow of carbohydrates to the sink centers [22,79]. The possibility of re-structuring the cell walls confirms the study of their structure in Brachypodium distachyon, which showed clear changes in the number and structure of polymers: cellulose, lignin, pectin and hemicelluloses.…”
Section: Regulation Of Source-sink Relations In the System "Depot Of ...mentioning
confidence: 71%
See 2 more Smart Citations
“…It is known that structural polysaccharides make up the bulk of the plant and in critical periods of growth and development can be incorporated in metabolism, probably providing a photosynthesis-independent flow of carbohydrates to the sink centers [22,79]. The possibility of re-structuring the cell walls confirms the study of their structure in Brachypodium distachyon, which showed clear changes in the number and structure of polymers: cellulose, lignin, pectin and hemicelluloses.…”
Section: Regulation Of Source-sink Relations In the System "Depot Of ...mentioning
confidence: 71%
“…It is believed that the evolutionary prerequisite for the ejection of the sourcesink system is the formation of the vascular system, which provides not only the vertical position of the plant in space, but also the transport, mechanical and spare functions in the plant. As the phloem is the major transport pathway for aminoacids and organic nitrogen from source to sink [10,79], it eliminates the possibility of regulating the source-sink pressure gradient by altering the activity of transport proteins that mediate cellular export and import through the apoplast. Such transport is effective in highly specialized sieve-like elements of the phloem, even in the tallest trees [8,54].…”
Section: The Main Aspects Of the Concept Of Source -Sinkmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants with high Lxx titers also showed the highest sucrose, maltose in the leaf and maltose in the culm, which occurred by reduced sugar partitioning to tillers production(Garcia et al, 2021). Symptomatic plants presented higher biomass in main culm, which caused higher sugars storage in parenchyma of the culm due to the lower tillers biomass(Garcia et al, 2021;Saez et al, 2019). However, the plants with high Lxx titers showed a decrease in trehalose content on the leaf when compared to low Lxx titers.…”
mentioning
confidence: 99%